2017
DOI: 10.2495/sdp-v12-n3-446-456
|View full text |Cite
|
Sign up to set email alerts
|

Urban facilities management: A systemic process for achieving urban sustainability

Abstract: With cities at the forefront of the challenge of achieving global sustainability, a key concern for urban management bodies is to identify ways to promote sustainable development at the urban and suburban level. Assessment mechanisms have dominated this field for the past two decades, and sustainable community assessment tools (SCATs) are fast becoming the principal framework adopted by urban planners and developers to drive sustainability. This paper investigates the efficacy and applicability of this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…There are a number of concerns about approaching complex development challenges through the simplified application of metrics. Many argue that such mechanisms undermine meaningful attempts to examine the structures and processes that define urban development and sustainability [7,8].…”
Section: An Overview Of Neighborhood Sustainability Assessment Toolsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are a number of concerns about approaching complex development challenges through the simplified application of metrics. Many argue that such mechanisms undermine meaningful attempts to examine the structures and processes that define urban development and sustainability [7,8].…”
Section: An Overview Of Neighborhood Sustainability Assessment Toolsmentioning
confidence: 99%
“…Various studies on NSA tools found that they are fundamentally dominated by environmental criteria [4,12,16,36,37,39]. As a result, NSA techniques "gloss over" considerations for social and economic aspects of sustainability [5], and the human factor of sustainability is vastly under-represented [8]. Hence, sustainability assessment has been unable to capture what makes the built environment sustainable for its citizens [14], and assessment rarely provides information that is relevant to manage the behavior of individuals [39,44].…”
Section: Environmental Bias and The Lack Of Appropriate Socio-economimentioning
confidence: 99%
See 3 more Smart Citations